PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA BENGKEL MOTOR AHASS UD “SURYA PERDANA INDAH” SUMBERREJO - Nurul Mazidah (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2012)
Today's business world of competition is getting tougher. It is also felt in the service businesses serve two-wheeled vehicles. UD AHASS bike shop Perdana Surya Indah is one of the official bike shop is in Sumberrejo HONDA. UD AHASS workshop Surya Indah Prime should know the factors that affect customer satisfaction and should make some improvements and innovations that can increase customer satisfaction. This study aims to analyze the impact of service quality views of five dimensions: direct evidence, reliability, responsiveness, assurance and empathy towards customer satisfaction service fees motors UD Perdana Surya Indah Sumberrejo. This research is being hypothesized that service quality has a significant influence on customer satisfaction. The sampling technique used is accidental sampling method, sampling is done randomly. The samples in this study were 100 men in the study analyzes customer using validity and reliability, the classic assumption test, multiple linear regression analysis, hypothesis testing via the F test and t test, and analysis of the coefficient of determination (R2). These five dimensions of service quality are the most dominant influence in the study there was a variable-empathy. The coefficient of determination shown by the Adjusted R Square is equal to 0.364, which means that the variation of all the independent variables can explain variable customer satisfaction by 36.4% and the remaining 63.6% described other independent variables.